ترجيحات الإمام الصابوني في روائع البيان تفسير آيات الأحكام من القرآن جمعاً ودراسة سورة البقرة أنموذجاً - بن بوذينة, لخضر (University of Eloued جامعة الوادي, 2018)
" ملخص الرسالة العنوان: ""ترجيحات الصابوني في روائع البيان تفسير آيات الأحكام من القرآن جمعا ودراسة سورة البقرة أنموذجا "" تهدف هذه الرسالة إلى جمع ترجيحات الصابوني التفسيرية ودراستها وبيان صيغ الترجيح والقواعد التي اعتمدها في تحرير الوجه الراجح في المسائل الفقهية , ويعتبر الاتجاه الذي انتهجه الشيخ الاتجاه الفقهي في التفسير وقد اعتمد على صيغ صريحة في الترجيح وفق القواعد الترجيح القرآن والسنة وبأقوال العرب وما يقتضيه السياق والعقل الإسلامي وكانت جل ترجيحاته موافقة لرأي الجمهور، ولتحقيق هذه الأهداف قسمت هذه الدراسة إلى مقدمة وتمهيد وفصلين وخاتمة وفهارس فنية, تناولت فيها أهمية الموضوع , أسباب الاختيار و الأهداف والإشكالية , أمّا المبحث التمهيدي : تناولت فيه التعريف اللغوي يبن الاختيار والترجيح والفرق بينهما, الفصل الأول تناولت فيه التعريف بالمؤلَف والمؤلَف ذكرت سيرة مختصرة عن الشيخ ورحلته للطلب العلم واهم شيوخه وتلاميذه وذكرت فيه التعريف بالمؤلف وتطرقت إلى مقاصده وميزاته وطباعته وآراء العلماء عليه. أمّا الفصل الثاني تناولت فيه منهج الصابوني في كتابه وصيغ الترجيح وقواعده وموقفه من بعض العلوم ورأيه في الخلاف في آيات الأحكام , كما تناولت الجانب التطبيقي للبحث من خلال سورة البقرة , خاتمة تناولت فيها أهم النتائج والتوصيات، وختمت البحث بفهارس فنية كاشفة لمضامين البحث " "Message summary Title: ""The weight of the Sabouni in the masterpieces of the statement interpretation of verses verses from the Koran Assembly and study Surat Al-Baqarah model"" The aim of this thesis is to collect the weights of the Sabouni interpretation and study the weighting formulas and rules adopted by the editor in the face of the most correct in the jurisprudential issues. The direction taken by the Sheikh is considered the jurisprudential direction of interpretation and was based on explicit formulas in weighting according to the weighting rules Quran and Sunnah The results of this study were divided into an introduction, a preface, two chapters, a conclusion, and a technical index, in which the importance of the topic, the reasons for selection, objectives and the problem were discussed. In the language of choice and build the weighting and the difference between them, the first chapter dealt with the definition of author and author A short biography of the Sheikh and his trip to the request of science and the most important elders and disciples And mentioned the definition of the author and touched on the purposes and features and printing and opinions of scientists on it. The second chapter dealt with the method of the Sabouni in his book and the weighting formulas and rules and his position on some of the sciences and his opinion in the dispute in the verses of the judgments. It also dealt with the practical aspect of the research through Surah Al-Baqarah. The conclusion dealt with the most important findings and recommendations. The research concluded with technical indexes revealing the contents of the research. "
مذكرة ماستر تخصص تفسير وعلوم القرآن
Keywords: "لخضر باك 2013 "; lakhdar bak2013